Posted by Alicia on Friday, July 31, 2009 at 9:03am.
Let f(x) = e^(x – 2) + 3.
Describe in words how the graph of f can be obtained from the graph of y = e^x.

Algebra  bobpursley, Friday, July 31, 2009 at 9:30am
starting with the graph of y=e^x.
move it up three units.
move it to the right two units. 
Algebra  Alicia, Friday, July 31, 2009 at 11:12am
What does this mean exactly? How can I put this in to a sentence to answer the question? Thank you!
Describe in words how the graph of f can be obtained from the graph of y = e^x.